Programming WCF services. - Löwy, Juval, ....- (Beijing : O'Reilly, 2007)
Written by Microsoft Software Legend Juval Lowy, "Programming WCF Services" is the authoritative introduction to Microsoft's new, and some say revolutionary, unified platform for developing Service-Oriented Applications (SOA) on Windows. Relentlessly practical, the book delivers insight, not documentation, to teach developers what they need to know to build the next generation of SOA's. After explaining the advantages of service-orientation for application design and teaching the basics of how to develop SOA's using WCF, the book shows how you can take advantage of built-in features such as service hosting, instance management, asynchronous calls, synchronization, reliability, transaction management, disconnected queued calls and security to build best in class applications. "Programming WCF Services" focuses on the rationale behind particular design decisions, often shedding light on poorly-documented and little-understood aspects of SOA development. Developers and architects will learn not only the "how" of WCF programming, but also relevant design guidelines, best practices, and pitfalls. Original techniques and utilities provided by the author throughout the book go well beyond anything that can be found in conventional sources. Based on experience and insight gained while taking part in the strategic design of WCF and working with the team that implemented it, "Programming WCF Services" provides experienced working professionals with the definitive work on WCF. Not only will this book make you a WCF expert, it will make you a better software engineer. It's the Rosetta Stone of WCF.